Is Public Information Openness the Key to Unlocking Justice in Indonesia’s State Administrative Court? - Maharani, Desty Puspita; Herlambang, Pratama Herry; Arifin, Ridwan (Indonesian State Law Review, 2024)
The principle of public information openness is a cornerstone of democratic governance, yet its implementation within Indonesia’s State Administrative Court remains underexplored. This research addresses the urgent need to assess how transparency and public access to information can enhance justice in administrative litigation. In a time when citizen trust in the legal system is fragile, and the accessibility of court decisions is increasingly crucial, the study explores whether the openness of public information can serve as a catalyst for greater accountability and fairness in the administrative justice system. The novelty of this research lies in its critical examination of the relationship between information transparency and judicial effectiveness in the context of administrative courts. By analyzing existing practices and identifying gaps in public access to court processes, the study presents an innovative approach to improving the delivery of justice. Through qualitative case studies and a comparative analysis of international practices, the research proposes actionable recommendations for reform. This study contributes to ongoing discussions on judicial transparency and its impact on public perception, aiming to create a more open, inclusive, and accountable State Administrative Court. The findings suggest that public information openness is not merely a procedural formality, but a fundamental aspect of building trust in the judiciary and empowering citizens in their pursuit of justice.